The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0162983
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis and Characterisation of the Exopolysaccharide Produced by Bifidobacterium longum subsp. longum 35624™

Abstract: The Bifibobacterium longum subsp. longum 35624™ strain (formerly named Bifidobacterium longum subsp. infantis) is a well described probiotic with clinical efficacy in Irritable Bowel Syndrome clinical trials and induces immunoregulatory effects in mice and in humans. This paper presents (a) the genome sequence of the organism allowing the assignment to its correct subspeciation longum; (b) a comparative genome assessment with other B. longum strains and (c) the molecular structure of the 35624 exopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 79 publications
1
43
0
7
Order By: Relevance
“…Notably, such novel findings imply that capsular structures of bifidobacteria play an important role in their host against pathological cell shedding (407). Furthermore, it has been shown that EPS produced by B. longum 35624 exerts an immune modulatory role by dampening proinflammatory host responses, while loss of EPS production results in the induction of local TH17 responses (408,409).…”
Section: Bifidobacteria and The Gut Microbiota Of Infantsmentioning
confidence: 99%
“…Notably, such novel findings imply that capsular structures of bifidobacteria play an important role in their host against pathological cell shedding (407). Furthermore, it has been shown that EPS produced by B. longum 35624 exerts an immune modulatory role by dampening proinflammatory host responses, while loss of EPS production results in the induction of local TH17 responses (408,409).…”
Section: Bifidobacteria and The Gut Microbiota Of Infantsmentioning
confidence: 99%
“…We recently described that the B. longum 35624 strain-specific EPS gene cluster, designated the EPS 624 cluster, is responsible for the production of a cell surface-associated exopolysaccharide (sEPS) composed of a branched hexasaccharide repeating unit with two galactoses, two glucoses, galacturonic acid, and the unusual sugar 6-deoxytalose (23). The overall aim of the current study was to determine whether the exopolysaccharide produced by B. longum 35624 is related to the immunoregulatory effects of this microorganism.…”
mentioning
confidence: 99%
“…The exopolysaccharide was isolated as previously described (23). Briefly, following harvesting of B. longum 35624 cells, which were grown on agar plates to minimize carryover of medium components, an exopolysaccharide solution was generated by agitating the cells in phosphate-buffered saline (PBS).…”
mentioning
confidence: 99%
“…Furthermore, very recent genomic analyses have reclassified B. infantis 35624 as B. longum subsp. longum 35624 11,12 . This further underscores the importance of using strain designations (35624) rather than genus/species to identify individual strains, and highlights that the Yuan et al meta-analysis does not, therefore, even include probiotic organisms belonging to the same sub-species.…”
mentioning
confidence: 99%